Social leadership, the motor for management practices in education in contexts of confinement - Marcela Gaete Vergara; Universidad de Chile; Violeta Acuña Collado; Universidad de Playa Ancha; Marisol Ramirez Muga; Universidad de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
Research on the field has provided enough evidence about the importance of the management leadership regarding schools' quality and students' learning. In respect to this, a series of politics has been designed to determine the competences related to an effective management performance. Nevertheless, the results of a qualitative and explanatory piece of research, in which 65 formal and non-formal formative projects  in education in context of confinement from Santiago, Chile participate, shows clear questionings on these policies in prison contexts. The participants of the study share a social leadership, focused on people's life circumstances and needs, which is the driving force for people who act based on the clear awareness of transformation. The psychosocial dimension is a relevant component to comprehend the arrival, the relationships, the manners and the persistency of formative projects carried out in the field of education in contexts of confinement. It is not about discrediting the relevance of management leadership but it is about questioning its reduction to a mere management as a political option inherited from neoliberal societies, which people in charge of these formative projects put in check on a daily basis